O extrativismo do calcário: impactos ambientais e socioeconômicos gerados na comunidade de Palheiros III, município de Upanema/RN - Silva, Aldefran Aderson da (Universidade Federal Rural do Semi-Árido, 2019)
It can be seen that the contemporary world is experiencing the height of technological advances, as well as the predominance of human beings over nature, a fact that creates a great withdrawal flow of raw material and natural resources for various purposes to be used by man. Reflecting on this process, the present work seeks to understand how the practice of limestone extraction is made by the dwellers of the community of Palheiros III, in the town of Upanema / RN, and what are the environmental and socioeconomic impacts generated by this practice. For this work, it was used the bibliographical research through several readings of materials that support the subject under discussion, such as articles, dissertations, books, final papers and others. In order to achieve the objectives, it was made the observation in the workplace, which is known as a quarry, and to obtain more specific data, it was applied a questionnaire to an audience of 20 respondents. By analyzing the results, it was understood that this was a critical issue, which generates loss of fauna and flora, affects the health of the worker and leaves them in economic decay, requiring immediate intervention. Faced with this, a lecture was held with some physiotherapists, to inform workers about the problems that can affect their health through this practice, and it is possible to provide them with adequate methods to work and have a healthier life. In addition, a field class was held in the quarry with the elementary students (final years) of the Escola Municipal 13 de Maio (May 13th Municipal School). This time, the students interviewed the workers and made observations in the environment, in order to understand the environmental and socioeconomic impacts, alluding to the importance of environmental education. Given this, it is regarded that the issue, reflected in the field of study, occurs due to the lack of access to an environmental education that leads to reflection on the impacts of such practice.
Monografia
Keywords: Extrativismo; Impactos; Socioeconômico; Ambiental; Palheiros III; Extractivism; Impacts; Socioeconomic; Environmental; Palheiros III; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO RURAL